Valorisation and categorisation of the geosites in the Podtatrze area (Southern Poland) // Waloryzacja i kategoryzacja geostanowisk na Podtatrzu (Polska południowa) - Chrobak, Anna (Geotourism/Geoturystyka, 2017)
The aim of this paper is to propose, valorise and categorise the geosites in the Podtatrze Area (Southern Poland). There are 46 geosites available in geodatabases (PGI, PAS and AGH) at this area. The author suggests next 28 geopoints, which can be used in geotourism. They were valorised by the Pereira and Pereira (2010) and Rybár (2010) methods and categorised. This area contains multiple geotourism attractions including interesting flysch geological settings, landslides, peatbogs, limestone klippes, various types of rivers with small gorges and paleontological sites. The increase in the number of tourists in the Podtatrze region may additionally provide numerous tangible benefits in the future, including sustainable tourism, less “congestion” in the Tatra Mountains, more economic diversity and new job opportunities. //